2021
DOI: 10.1007/s00266-021-02198-3
|View full text |Cite|
|
Sign up to set email alerts
|

Does Overfilling Smooth Inflatable Saline-Filled Breast Implants Decrease the Deflation Rate? Experience with 4761 Augmentation Mammaplasty Patients

Abstract: Background Research suggests that overfilling saline inflatable breast implants may decrease their deflation rates. To date, there has been no large-scale study comparing breast implants filled within vs. beyond the manufacturer’s recommended fill volumes. Methods A retrospective comparative study was conducted for 4761 women who underwent aesthetic augmentation mastopexy by the author. Patients were divided into two groups: Group 1 includes 2960 patients … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
1
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 24 publications
(41 reference statements)
0
1
0
Order By: Relevance
“…With regard to deflation rates, a study done by Eisenberg showed that females with breast implants filled above the manufacturers recommended fill volumes as opposed to those within the recommended fill volumes showed a significantly reduced deflation rate. 3 Furthermore, in another study done by Al-Sabounchi, it was shown that filling Mentor 2600 prostheses to a level above the recommended guidelines led to increased longevity of the breast implants and as well had a significant effect on the 10-year survival rate of the implants. 2 Future research into determining the optimal levels for shell filling of MemoryGel Xtra implants and their impact on various complications can potentially contribute to increased overall performance of breast implants and can guide the development of even more advanced and tailored devices.…”
mentioning
confidence: 98%
See 1 more Smart Citation
“…With regard to deflation rates, a study done by Eisenberg showed that females with breast implants filled above the manufacturers recommended fill volumes as opposed to those within the recommended fill volumes showed a significantly reduced deflation rate. 3 Furthermore, in another study done by Al-Sabounchi, it was shown that filling Mentor 2600 prostheses to a level above the recommended guidelines led to increased longevity of the breast implants and as well had a significant effect on the 10-year survival rate of the implants. 2 Future research into determining the optimal levels for shell filling of MemoryGel Xtra implants and their impact on various complications can potentially contribute to increased overall performance of breast implants and can guide the development of even more advanced and tailored devices.…”
mentioning
confidence: 98%
“…This concept is grounded in experiences with saline-filled implants, with which maximal filling has been associated with reduced wrinkling and rippling and a prolonged implant life span. 3 The design of MemoryGel Xtra implants incorporates this idea, optimizing gel fill to enhance central device fullness and projection while minimizing surface wrinkling. The authors express their expectation that continued observation over the next 7 years will reveal whether these precision-filled implants indeed lead to enhanced long-term results.…”
mentioning
confidence: 99%
“…For the last 40 years, the predominant approach has been to place the tissue expander and implant deep to the pectoralis major muscle, often requiring mobilization of serratus anterior and rectus abdominis fascial flaps to provide lateral and inferior implant coverage, respectively 2–4 . Subpectoral tissue expanders are often overfilled to enhance breast projection 5 . Despite satisfactory implant coverage, support, and cosmetic outcomes, the subpectoral approach poses risks from pectoralis elevation including pain, animation deformity, implant lateralization, poor inframammary fold definition, and revision rates as high as 30% 4,6,7 .…”
mentioning
confidence: 99%